ORGANIC ACIDS PRODUCTION OF RICE STRAW FERMENTED WITH SEVERAL TYPES OF MICROORGANISM AT DIFFERENT TEMPERATURES - Yanti, Y.; Surahmanto, S.; Purnomoadi, A.; Kawamoto, Y. (Diponegoro University, 2012)
The experiment was carried out to examine the organic acids production of rice straw fermentedwith some types of microorganisms at different temperatures. The experiment was designed as SplitPlot-Completely Randomized Design. The main plot was temperatures treatments (25, 35, 45°C) and thesub plot were microorganisms (Control, Control+Mollases, Lactobacillus fermentum, Bacillus subtilis,Bacillus coagulant, Saccharomyces cerevisiae, Aspergillus niger). The highest lactic acid productionswas in B. coagulans treatment at 35°C (53.79 g/kg DM). The highest acetic acid productions was in L.fermentum at 35°C (13.20 g/kg DM), while the highest propionic acid productions were in Controltreatment at 35°C (0.37 g/kg DM).